2022
DOI: 10.1155/2022/6481697
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Rapid Rehabilitation Effect of Children with Severe Viral Encephalitis Based on Continuous Nursing of Omaha System

Abstract: Objective. To establish the Omaha System-based intensive care of children with viral encephalitis, compared with the conventional nursing applied in children with severe viral encephalitis for children with clinical symptoms, motor function, the incidence of complications, and the influence of quality of life, to intensive care of children with viral encephalitis way provide certain scientific basis. Methods. 62 cases of severe viral encephalitis diagnosed and treated in our hospital from X month 20XX to X mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As indicated in the included studies (Table 1), routine The use of RRN has been steadily increasing, fueled by the growing body of evidence suggesting its potential benefits in postoperative care (Liang et al, 2021). Some studies have reported positive outcomes associated with RRN, such as reduced postoperative pain, improved physical function, shortened hospital stays, and a lower incidence of complications (Chang et al, 2022;Chen et al, 2023;Feng et al, 2022;Ji & Yan, 2023). In addition, RRN has been shown to enhance patient satisfaction with nursing care and contribute to better resource utilization in healthcare settings (Ross et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated in the included studies (Table 1), routine The use of RRN has been steadily increasing, fueled by the growing body of evidence suggesting its potential benefits in postoperative care (Liang et al, 2021). Some studies have reported positive outcomes associated with RRN, such as reduced postoperative pain, improved physical function, shortened hospital stays, and a lower incidence of complications (Chang et al, 2022;Chen et al, 2023;Feng et al, 2022;Ji & Yan, 2023). In addition, RRN has been shown to enhance patient satisfaction with nursing care and contribute to better resource utilization in healthcare settings (Ross et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%